The cult of the White Old Man: Mongolian texts from Tuva - Bicheev, Baazr A.; Aoqier, Alateng (The New Research of Tuva, 2021)
One of the richest ritualistic, textual and iconographic traditions is associated with the cult figure of the White Old Man. Its popularity and significance makes it a remarkable phenomenon in the religious and spiritual culture of Mongolians. The aim of this article is to give an overview of the Mongolian texts of sang-prayers and of the "Sutra of the White Old Man", which are a part of the collections of the Aldan Maadyr National Museum of the Republic of Tuva. The manuscript collection of the museum boasts of eleven such manuscripts, and five of these, examined by the authors, are presented in this publication. The Tuvan manuscripts are of special interest as illustrative of the regional tradition of the White Old Man worship, but also in terms of the textual studies. One of the features of the graphics of Tuvan texts is that the grapheme š is in most cases marked with a crown (titm) in all positions, which is a typical feature of "clear script".